2016
DOI: 10.4278/ajhp.150212-quan-724
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Policy and Environmental Change in Faith-Based Organizations: Description and Findings From a Mini-Grants Program

Abstract: The church environment may play an important role in supporting healthy eating in this setting and more generally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
0
26
0
Order By: Relevance
“…5,6 Churches' physical infrastructure, programs, and social networks can be leveraged to influence not only individuals but also the congregation and neighborhood. 7 Previous church-based interventions with AAs and Latinos have influenced eating and/or physical activity habits through educational approaches, 8,9 changes to the food environment at church, 10,11 on-site exercise get-togethers, 12 and neighborhood walkability assessments and advocacy. 13 However, such interventions have been limited by challenges with reaching participants for intervention activities and measurement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Churches' physical infrastructure, programs, and social networks can be leveraged to influence not only individuals but also the congregation and neighborhood. 7 Previous church-based interventions with AAs and Latinos have influenced eating and/or physical activity habits through educational approaches, 8,9 changes to the food environment at church, 10,11 on-site exercise get-togethers, 12 and neighborhood walkability assessments and advocacy. 13 However, such interventions have been limited by challenges with reaching participants for intervention activities and measurement.…”
Section: Introductionmentioning
confidence: 99%
“…14 Congregants' busy schedules may limit their ability to attend in-person activities, 9 and long-term follow-up with participants can be difficult. 8 Furthermore, while the church environment is important, the home environment remains key, 7 suggesting a need to engage with congregants outside of the church setting.…”
Section: Introductionmentioning
confidence: 99%
“…This incremental approach ensured buy-in and gave both the community organization and funder the option to continue. Similar to others who have used mini-awards to maximize resource distribution in public health (Arriola et al, 2016;Wiebel, Welter, Aglipay, & Rothstein, 2014), this initiative demonstrated similar success.…”
Section: Lessons Learnedmentioning
confidence: 55%
“…Shared use (working with organizations to open access to their facilities) is a promising strategy for increasing the number of safe and accessible spaces to be physically active ( 3 , 4 ). Although researchers have examined the prevalence of shared-use agreements in schools, little is known about implementation of and barriers to shared use of recreational facilities in faith-based settings ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Public health practitioners have harnessed this potential by implementing and evaluating obesity prevention programs that have included lay advisor models ( 7 , 8 ), targeted diabetes education ( 7 ), and community-based participatory research ( 9 , 10 ). Researchers have documented and evaluated how faith communities implement healthful eating or physical activity policies, provide spaces or time for physical activity, and promote access to healthful foods ( 5 , 8 ).…”
Section: Introductionmentioning
confidence: 99%